The role of freshwater snails in the transmission of influenza A viruses - Oesterle, Paul Thomas, author; Huyvaert, Kathryn P., advisor; Root, J. Jeffrey, advisor; Bowen, Richard, committee member; Myrick, Christopher, committee member (Colorado State University. Libraries, 2011)
Waterfowl are the natural reservoirs for avian influenza (AI) viruses. Avian influenza virus infections in these birds are generally subclinical, but they shed infectious virus through feces for several days, typically into water. Further, AI viruses can remain infectious in water for weeks. This characteristic enhances transmission of AI viruses among waterfowl because transmission is not constrained by direct contact. The prevalence of AI virus infection in waterfowl populations follows a cyclical pattern; prevalence is highest in the population after the breeding season. Shedding of AI viruses is nearly undetectable in these waterfowl populations by winter, yet the prevalence cycle repeats itself annually. Somehow, AI viruses are reintroduced to host populations. The mechanisms that drive the prevalence patterns observed in waterfowl are likely numerous and complex, but AI viral persistence in water is probably critical. Persistence of AI viruses in water also potentially exposes other organisms to the virus. Aquatic invertebrates, such as snails, are likely exposed to AI viruses while feeding on detritus in aquatic habitats, and gastropods are a common food source for many species of waterfowl. This trophic interaction may potentially serve as an additional route of AI virus transmission and maintenance. In this study, two species of freshwater snails (Physa acuta and P. gyrina) were experimentally exposed to avian influenza virus (H3N8) to determine: 1) whether the snails have cellular receptors capable of binding to AI viruses, 2) whether snails can bioaccumulate AI viruses, 3) how long bioaccumulated AI viruses are maintained and remain infectious in snail tissues, and 4) whether Physa spp. can serve as mechanical vectors of AI viruses. My results indicated that, while Physa spp. snails sequestered infectious AI virus, the duration was short-lived and no transmission occurred. These data suggest that the snail species examined do not directly impact AI virus transmission among waterfowl; however, in the process of feeding on snails, waterfowl may be exposed to AI viruses both via water and ingestion such that other avenues of investigation are warranted.